Overview of high temperature fibre Bragg gratings and potential improvement using highly doped aluminosilicate glass optical fibres. (23rd August 2019) - Cavillon, Maxime; Lancry, Matthieu; Poumellec, Bertrand; Wang, Yitao; Canning, John; Cook, Kevin; Hawkins, Thomas; Dragic, Peter; Ballato, John
Abstract: In this paper, various types of high temperature fibre Bragg gratings (FBGs) are reviewed, including recent results and advancements in the field. The main motivation of this review is to highlight the potential of fabricating thermally stable refractive index contrasts using femtosecond (fs) near-infrared radiation in fibres fabricated with non-conventional techniques, such as the molten core method. As a demonstration of this, an yttrium aluminosilicate (YAS) core and pure silica cladding glass optical fibre is fabricated and investigated after being irradiated by an fs laser within the Type II regime. The familiar formation of nanogratings inside both core and cladding regions are identified and studied using birefringence measurements and scanning electron microscopy. The thermal stability of the Type II modifications is then investigated through isochronal annealing experiments (up to T = 1100 °C; time steps, Δ t = 30 min). For the YAS core composition, the measured birefringence does not decrease when tested up to 1000 °C, while for the SiO2 cladding under the same conditions, its value decreased by ∼30%. These results suggest that inscription of such ' Type II fs-IR ' modifications in YAS fibres could be employed to make FBGs with high thermal stability. This opens the door toward the fabrication of a new range of 'FBG host fibres' suitable for ultra-high temperature operation.